Transitional Leadership and Its Relation with Occupational Performance Creativity from Iraqi Ministry of Youth and Sport Employees’ Point of View - ahmed, anmar; Mohameed, Ahmed (Journal of Physical Education, 2023)
The research aimed at showing the effect of transitional leadership on creativity level of occupational performance in provinces and governorates centers in the ministry of Youth and Sports. The researchers constructed two scales; one for measuring transitional leadership and the other for creativity of occupational performance. They used the descriptive method on (300) employee in provinces and governorates centers of ministry of youth and sports. Two scales were constructed and distributed on the subjects then gathered to make the proper statistical operations to conclude that transitional leadership significantly affect creativity in occupational performance. The researchers recommended relaying on transitional leadership in provinces and governorates of the ministry.